The Effect of Good Corporate Governance (GCG), Temporary Syirkah Funds, and Profitability on the Performance of the Maqasid of Sharia Commercial Banks in Indonesia - Iftikar Arif Yuri; Annisaa Rahman; Amy Fontanela; Syamsurizal Syamsurizal (Universitas Pendidikan Indonesia, 2021)
AbstractPurpose –This study aims to examine the effect of good corporate governance, temporary syirkah funds and profitability to the performance of maqasid sharia that occurs in Islamic banks registered as sharia commercial banks within a period of five years with purposive sampling methodMethodology - This research type is quantitative research to get the data and information that the authors obtained from several Islamic Commercial Banks listed on the Indonesia Stock Exchange in 2012- 2016. Findings - The results showed that temporary syirkah funds had an effect on the performance of maqasid sharia. While Good Corporate Governance (independent board of commissioners, syariah supervisory board, DPS positions, audit committee), and profitability do not affect the performance of maqasid sharia.Keywords: Good Corporate Governance, independent board of commissioner, syariah supervisory board, DPS positions, audit committee, temporary syirkah fund, profitability, maqasid sharia. AbstractPurpose –This study aims to examine the effect of good corporate governance, temporary syirkah funds and profitability to the performance of maqasid sharia that occurs in Islamic banks registered as sharia commercial banks within a period of five years with purposive sampling method This study aims to explore and categorize research literature on Financial Technology in Islamic Capital Market systematically by mapping and visualizing it through bibliometric analysis using VOSviewer.Methodology - This research type is quantitative research to get the data and information that the authors obtained from several Islamic Commercial Banks listed on the Indonesia Stock Exchange in 2012- 2016. The research from publications that have appeared in journals that are indexed by Google Scholar served as the foundation for the article data used in this study. A reference manager tool called Publish or Perish is used to gather research data. A literature review on the subject we chose was done with the help of the program Publish or Perish. Findings - The results showed that temporary syirkah funds had an effect on the performance of maqasid sharia. While Good Corporate Governance (independent board of commissioners, syariah supervisory board, DPS positions, audit committee), and profitability do not affect the performance of maqasid sharia.The results show that research on Financial Technology in Islamic Capital Market is separated into 3 terms: Financial Technology, Islamic, Capital Market. The term